Novel Applications and Properties of Dynamic Foam - Tadvi, Aasma R.; Bathe, Ganesh A. (Chemical and Materials Sciences: Developments and Innovations Vol. 7, 2024)
Dynamic foam properties like Foam stability and foaminess were examined in this work. There are two ways to create surfactant foams: static and dynamic. Under the dynamic approach, foams are continuously produced and simultaneously eroding from the surface. Foam height rises when the rate of foam generation exceeds the rate of foam decay; height stays constant when the rate of foam generation and decay is equal. Lastly, when the rate of foam generation is lower than the rate of foam decay, the height of the foam drops. As surfactant foam provides a very high surface area per unit volume of the liquid, it can provide good heat and mass transfer between gas and liquid. The half-life of Sodium Lauryl Sulphate (SLS) foam at room temperature increased from 13.33 minutes to 28.33 minutes in the presence of nanoparticles (NPs). In this chapter, two applications of dynamic foam were studied. Novel applications of surfactant foam are in need of time, which essentially depends on its properties. Due to their unique properties, surfactant foams are utilized in numerous industrial applications, and it is expected that new applications for dynamic foam will emerge in the near future.